(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
Interaction of iodide anion complex of cadmium with basic dye crystal violet has been investigated. Formed ionic associate could be extracted by toluene–dichlorethan (2:1) binary mixture. Maximal light absorption is observed at λ=575–590 nm wavelengths. The optimal acidity of aqueous phase is pH 1, optimal concentration of crystal violet is 6.3·10–4–7.56·10–4 M and KI – 3·10–2–7·10–2 M. The range of determined concentration is 0.25–5.0 mcg/mL, ε585 = 97000±600 (L·mol–1·cm–1). The method was used for determination of cadmium contents in tobacco, milk, sour cream and curd. The method is more sensitive and simple than those reported earlier.